The vulnerability of calretinin-containing hippocampal interneurons to temporal lobe epilepsy - Tóth, Kinga; Maglóczky, Zsófia (Frontiers in Neuroanatomy, 2014)
This review focuses on the vulnerability of a special interneuron type—the calretinin (CR)-containing interneurons—in temporal lobe epilepsy (TLE). CR is a calcium-binding protein expressed mainly by GABAergic interneurons in the hippocampus. Despite their morphological heterogeneity, CR-containing interneurons form a distinct subpopulation of inhibitory cells, innervating other interneurons in rodents and to some extent principal cells in the human. Their dendrites are strongly connected by zona adherentiae and presumably by gap junctions both in rats and humans. CR-containing interneurons are suggested to play a key role in the hippocampal inhibitory network, since they can effectively synchronize dendritic inhibitory interneurons. The sensitivity of CR-expressing interneurons to epilepsy was discussed in several reports, both in animal models and in humans. In the sclerotic hippocampus the density of CR-immunopositive cells is decreased significantly. In the non-sclerotic hippocampus, the CR-containing interneurons are preserved, but their dendritic tree is varicose, segmented, and zona-adherentia-type contacts can be less frequently observed among dendrites. Therefore, the dendritic inhibition of pyramidal cells may be less effective in TLE. This can be partially explained by the impairment of the CR-containing interneuron ensemble in the epileptic hippocampus, which may result in an asynchronous and thus less effective dendritic inhibition of the principal cells. This phenomenon, together with the sprouting of excitatory pathway axons and enhanced innervation of principal cells, may be involved in seizure generation. Preventing the loss of CR-positive cells and preserving the integrity of CR-positive dendrite gap junctions may have antiepileptic effects, maintaining proper inhibitory function and helping to protect principal cells in epilepsy.